A terapia ocupacional no contexto de educação inclusiva: uma revisão da literatura com base no estado da arte - NEVES, Juliane Priscila Brasil (2023)
The present work was thought from the experience of the curricular internship within the educational area and is configured as a Course Completion Work, which discusses the practice of occupational therapy in the context of inclusive education. Inclusion is the central theme of world debates, as it is understood as a crucial factor for personal development; However, it is necessary to break historically established integrationist and exclusionary ideas; advances in public policies attempt to minimize this context. The occupational therapist is an important part of the present context, because it seeks the best engagement of the student. The general objective is: to analyze the insertion of occupational therapy in inclusive education through its intervention practices. The specifics are: To identify the methodological paths used by occupational therapists in inclusive practice and to categorize the production of knowledge about the occupational therapist in educational inclusion. The research is bibliographical based on the state of the art, which allows us to glimpse how the knowledge of the area has really constituted. The analysis of content allows, in addition to interpreting minutiae of the text, to categorize and to understand the work, which was done from the organization of the information in the table. In all sixty-nine (69) works were analyzed, among them articles of magazines, chapters and books and works in scientific events. The results evidenced a great repertoire of practices and subjects contemplated by the profession within the educational field, thus showing, several possibilities of insertion of the profession within this area of intervention, which is relatively new to it. It is concluded that the importance of disseminating practices in the context of inclusive education is of fundamental importance for both professionals and the community, since it seeks to establish the scientific knowledge of occupational therapy in this area of practice.